Envolvimento do receptor de angiotensina II tipo 1 nas alterações cardiovasculares induzidas pelo estresse crônico : comparação entre estressores homotípicos e heterotípicos - Ferreira, Willian Costa (2016)
Emotional stress has been recognized as a risk factor for cardiovascular diseases. Nevertheless, the mechanisms involved in the etiology of cardiovascular dysfunctions evoked by stress are still poorly understood. Thus, in the present study we investigated the involvement of angiotensin II acting in the type 1 receptor (AT1) in cardiovascular dysfunctions evoked by chronic stress in rats. For this, we compared the effect of chronic treatment with the AT1 receptor antagonist losartana (30mg/kg/day, p.o.) in the cardiovascular and autonomic changes following 10 days exposure to chronic variable stress (CVS, heterotypic stressor) and repeated restraint stress (RRS, homotypic stressor). Neither RRS nor CVS affected basal values of arterial pressure and heart rate. However, RRS increased sympathetic tone to the heart and decreased cardiac parasympathetic activity, whereas CVS decreased cardiac parasympathetic activity. Both chronic stressors also impaired the baroreflex function. All alterations in autonomic activity and the baroreflex impairment were inhibited by treatment with losartan. Complementary measurements of parameters commonly analyzed in studies investigating stress effects also indicated that CVS reduced body weight gain and increased circulating corticosterone, but these effects were not affected by losartan. In fact, CVS-evoked body weight change was even higher in losartan-treated animals. In conclusion, these findings indicate an involvement of angiotensin II/AT1 receptors in autonomic changes evoked by both homotypic and heterotypic chronic stressors. Additionally, present results suggest that increased circulating corticosterone evoked by CVS is independent of AT1 receptors, while reduction in body weight gain evoked by this heterotypic stressor is facilitated by treatment with losartan.